Fertilizantes fosfatados para a cana-de-açúcar aplicados em pré plantio (fosfatagem) - Sousa, Robson Thiago Xavier de (2011)
Phosphate application is still rarely used in sugarcane and can be done with phosphorus fertilizers of long residual period. This study evaluated the effect of phosphate fertilizers applied in the whole area before planting on sugarcane yield and technological quality. The study was done at Jalles Machado sugar-mill, in Goianésia-GO, during three growing seasons. The treatments consisted of five different phosphorus sources, soluble and insoluble, applied in the rate equivalent to 300 kg ha-1 P2O5. The fertilizers used were: triple superphosphate, mono-ammonium phosphate (MAP), Arad phosphate rock, Itafós phosphate rock and magnesium thermophosphate. The effects of these fertilizers were evaluated by analysis of plant height (height from ground to TVD), leaf phosphorus content, sugarcane yield in cane plant, first ratoon and second ratoon, by technology parameters in ratoon, by sugar produced and by agronomic efficiency. Application of magnesium thermophosphate and triple superphosphate resulted in greater plant cane height. Leaf concentrations of phosphorus in cane showed the superiority of MAP, magnesium thermophosphate and triple superphosphate. Phosphate applications did not affect yield of cane plant, but increased yield of sugarcane ratoon as well as the amount of sugar produced per hectare. In general, the residual effect of insoluble phosphates increased over the years. The Agronomic Efficiency Indices (AEI) of phosphate decreased in the following order: Triple superphosphate (100%)> Thermophosphate (89%)> MAP (80%)>Itafós phosphate rock (67%)> Arad phosphate rock (60 %).